A PRACTICAL APPROACH TO SWITCH FROM A MULTIPLE PILL THERAPEUTIC STRATEGY TO A POLYPILL-BASED STRATEGY FOR SECONDARY PREVENTION IN PATIENTS WITH HYPERTENSION. (April 2021) - Coca, Antonio; Kreutz, Reinhold; Manolis, Athanasios; Mancia, Giuseppe
Abstract : Objective: The recommendation in hypertension is to initiate treatment with a combination of two blood pressure-lowering drugs in a single pill regardless of the cardiovascular (CV) risk, to add a statin in patients with established CV disease (CVD) or at moderate or high risk, and to add as well an antiplatelet agent only among those with established CVD. Some clinical guidelines nowadays endorse the polypill approach to increase the efficiency of the pharmacological treatment and decrease CV morbidity and mortality. The CNIC polypill is the only CV polypill marketed in Europe and the only approved by the EMEA for the secondary prevention of CVD. This polypill contains aspirin, ramipril, and atorvastatin. We aimed at helping clinicians to start treatment with the CNIC polypill switching from any other statin to atorvastatin, and from any angiotensin-converting enzyme inhibitor (ACEI) or angiotensin II receptor blocker (ARB) to ramipril. Design and method: We looked for available data and recommendations to build tables of equivalent effective daily doses of two of the polypill components (ramipril and atorvastatin), and we developed a treatment algorithm based on expert opinion. Results: We provide the approximate equivalent effective daily doses of other ACEIs and ARBs with ramipril and of other statins according to atorvastatin's potency. Moreover, to guide clinicians in the management of patients for secondary prevention of CVD, we provide a treatment algorithm and detail the indications and different available preparations to start treatment with the CV polypill in patients with high BP and prior CVD, and how to associate other BP-lowering drugs or lipid-lowering drugs if need be. Finally, we give advice on how to switch and adapt the treatment of patients already on fixed-dose combinations of antihypertensive medications to initiate the CV polypill regimen. Conclusions: The multiple doses of the individual components of the CNIC polypill versions allow for increased flexibility in prescribing and use it to start treatment in patients with high BP and prior CVD, and probably also in the particular scenario of hypertensive patients at high CVD risk without previous CV event and no significant risk of major bleeding.